The twin deficits hypothesis and reverse causality: A short-run analysis of Peru - Sobrino, César R. (2013)
This study examines causation between the current account and the fiscal surplus and fiscal spending for a commodity-based economy, Peru. Using quarterly data for the open economy, the outcomes reject the twin deficits hypothesis. Instead, the evidence points strongly to reverse causality, that is, the current account causes the fiscal account. However, unlike previous empirical evidence on this subject, for a year, the reverse causality indicates a negative causation because the fiscal consumption is not smoothed when positive permanent shocks to the current account occur. In the short run, the fiscal policy has no effect on the current account, but improvements in the current account increase the probability of attaining a lower bounded fiscal deficit. This evidence is consistent with a small open commodity-based economy that is highly exposed and sensitive to external price shocks.